Prevalence of Coxiella burnetii antibodies in bulk milk and blood serum and associations with reproductive indices in cow dairy herds of Central and Northern Greece - DOVOLOU (Ε. ΝΤΟΒΟΛΟΥ), E.; TSILIGIANNI (Θ. ΤΣΙΛΙΓΙΑΝΝΗ), Th.; VOUZARAS (Δ. ΒΟΥΖΑΡΑΣ), D.; AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), G. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
For the first time in Greece, we investigated the prevalence of Coxiella burnetii antibodies in milk and sera from dairy cattle herds located at central and northern parts of the country. Eighty herds were initially voluntary enrolled in the study and a bulk milk sample from each farm was assayed by ELISA for C burnetii antibodies. According to antibody titre, herds were classified into 5 categories: negative and grades 1,2,3 and 4 (ascending scale). To assess the prevalence within farms, two herds from each category were selected and blood samples were collected for antibody assessment. In these herds, some reproductive indices were compared between farms; in addition, comparisons were made in paired seropositive and seronegative animals from one grade 3 herd. Twenty three herds (35%) were found positive, 21 being in categories 3 and 4. The prevalence of seropositive animals between herds varied from 4.9 to 46.3%, even from farms initially characterized as negative, some positive animals were detected. Between farms, no differences were detected in the abortion rate or in the mean number of artificial inseminations (AI) per pregnancy. Some differences were found in other reproductive indices that were impossible to be biologically interpreted under the light of C. burnetii level of infection. From the results presented here, we infer that C. burnetii infection is likely asymptomatic in dairy cows causing minimal -if any- economic losses to farmers. However, since the disease is a zoonotic one, its spread can easily occur, a systematic surveillance, in all ruminant species, for the restriction or eradication of the disease should be undertaken in national level.